1975
DOI: 10.1113/jphysiol.1975.sp011197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II on fluid transport, transmural potential difference and blood flow by rat jejunum in vivo.

Abstract: SUMMARY1. A method has been described for the measurement of fluid transport by rat jejunum in vivo over two consecutive 30 min periods.2. Subpressor infusion rates of angiotensin (0.59 ng/kg per minute) stimulate fluid transport, while high (pressor) infusion rates (590 ng/kg per minute) inhibit fluid absorption.3. Both the inhibitory and stimulatory effects of angiotensin on fluid transport are not accompanied by any change in the transmural p.d., total blood flow to the jejunum or distribution of blood flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…Angiotensin II (ANG II) regulates sodium and water transport across epithelial cells in the kidney and gastrointestinal tract (1)(2)(3)(4)(5). In the jejunum, low concentrations of ANG II stimulate sodium and water absorption while high concentrations inhibit absorption and/or stimulate secretion (3).…”
Section: Introductionmentioning
confidence: 99%
“…Angiotensin II (ANG II) regulates sodium and water transport across epithelial cells in the kidney and gastrointestinal tract (1)(2)(3)(4)(5). In the jejunum, low concentrations of ANG II stimulate sodium and water absorption while high concentrations inhibit absorption and/or stimulate secretion (3).…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal fluid transport was measured in vivo by the method of Bolton, Munday, Parsons & York (1975). Fluid absorption in anaesthetized animals (given as ml.…”
Section: P Proceedings Of Thementioning
confidence: 99%
“…Department of Physiology and Biochemistry, University of Southampton Recent evidence has shown that noradrenaline stimulates electroneutral intestinal absorption in vitro (Brasitus, Field & Kimberg, 1977). Furthermore the hormone angiotensin stimulates electroneutral fluid absorption in vivo in the absence of changes in blood flow (Bolton, Munday, Parsons & York, 1975), and also releases noradrenaline both from sympathetic nerve endings and from the adrenal medulla (Peach, 1974). The following experiments were carried out to compare the effects of angiotensin and noradrenaline on intestinal fluid transport in vivo.…”
Section: Pmentioning
confidence: 99%
“…Closed sacs of rat jejunum filled with Krebs' bicarbonate saline containing either [3H]inulin or [14C]polyethylene glycol, to act as a nonabsorbable marker, were prepared as described by Bolton et al (1975). A control period of isotonic saline infusion at 1 ml.…”
Section: Pmentioning
confidence: 99%